2009
DOI: 10.1577/m08-056.1
|View full text |Cite
|
Sign up to set email alerts
|

Maturation and Reproduction of Shovelnose Sturgeon in the Middle Mississippi River

Abstract: Shovelnose sturgeon Scaphirhynchus platorynchus in the middle Mississippi River provide one of the last commercially viable sturgeon fisheries in the world, yet their maturation and reproduction have not been linked. During 2005 and 2006, we sampled adult and age‐0 shovelnose sturgeon to link age at maturation, the timing and periodicity of spawning, age‐0 sturgeon production, and the resulting age‐0 growth rates. Age at maturity was later than previous estimates, the minimum age of first maturation being 8 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
78
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(84 citation statements)
references
References 24 publications
5
78
1
Order By: Relevance
“…We assumed that the length when growth begins to asymptote was related to the size at reproductive maturity. This assumption was based on several studies examining the reproductive biology of shovelnose sturgeon that reported sexual maturity in the Missouri River and the lower Platte River at approximately 450 mm (Moos 1978;Rugg 2013), whereas fish from the upper and middle Mississippi River and the Wabash River were first mature at approximately 570-615 mm (Kennedy et al 2006;Koch et al 2009;Tripp et al 2009b). The length at maturity of shovelnose sturgeon varied by locations and appeared to be influenced by abiotic or biotic factors.…”
Section: Discussionmentioning
confidence: 99%
“…We assumed that the length when growth begins to asymptote was related to the size at reproductive maturity. This assumption was based on several studies examining the reproductive biology of shovelnose sturgeon that reported sexual maturity in the Missouri River and the lower Platte River at approximately 450 mm (Moos 1978;Rugg 2013), whereas fish from the upper and middle Mississippi River and the Wabash River were first mature at approximately 570-615 mm (Kennedy et al 2006;Koch et al 2009;Tripp et al 2009b). The length at maturity of shovelnose sturgeon varied by locations and appeared to be influenced by abiotic or biotic factors.…”
Section: Discussionmentioning
confidence: 99%
“…() and Tripp et al. () (Table ). Individuals were classified as spawners if they had mature ovarian follicles (hereafter referred to as oocytes) or sperm in their gonads, showed evidence of previously carrying mature gametes or were recently spent.…”
Section: Methodsmentioning
confidence: 95%
“…() and Tripp et al. () (Table ). A McNemar's test was used to compare the classification of sex and stage (binary outcomes) from visual inspections to histological samples.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…Pallid sturgeons were classified as wild or hatchery-reared according to the presence of a hatchery mark and/or tag or by post hoc genetic determination DeHaan et al 2008). Gender and gonad maturation stage were determined using ultrasound and endoscopic techniques described in Bryan et al (2007) and Divers et al (2009) and fish categorized as reproductive (stage IV, ready to spawn this season) or non-reproductive (stage IIÀIII; Moos 1978; Colombo et al 2007;Tripp et al 2009). The number of eggs released was estimated using volumetric estimation by counting a subset of number of eggs/mL and extrapolating to the total volume extracted.…”
Section: Methodsmentioning
confidence: 99%